If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(6)(h) + 2(h)(17) + 2(6)(17) = 342 Multiply 2 * 6 12h + 2(h)(17) + 2(6)(17) = 342 Reorder the terms for easier multiplication: 12h + 2 * 17h + 2(6)(17) = 342 Multiply 2 * 17 12h + 34h + 2(6)(17) = 342 Multiply 2 * 6 12h + 34h + 12 * 17 = 342 Multiply 12 * 17 12h + 34h + 204 = 342 Reorder the terms: 204 + 12h + 34h = 342 Combine like terms: 12h + 34h = 46h 204 + 46h = 342 Solving 204 + 46h = 342 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-204' to each side of the equation. 204 + -204 + 46h = 342 + -204 Combine like terms: 204 + -204 = 0 0 + 46h = 342 + -204 46h = 342 + -204 Combine like terms: 342 + -204 = 138 46h = 138 Divide each side by '46'. h = 3 Simplifying h = 3
| 6x=x+6 | | 2(6)(h)+2(h)(17)+2(6)(17)=h | | 12.5y+30+130-30=180 | | 13x-30=100 | | 9r=81 | | (2k+1)(2m+1)= | | -2-ln(x+1)=0 | | 20x^2-2x-4=0 | | 72x^2+96x-936=0 | | 4x+-6=34 | | -2x-(-8+3x)=6 | | y=-3x+-8 | | 3x+12-7*3x=123 | | (y+7)(y-8)= | | 72x^2-2496x-936=0 | | 98-7(10)= | | 98-7(-5)= | | (8x+1)-(-5x+5)= | | 98-7(280)= | | 2x^2-18x+45=0 | | y=5E-06x+0.24 | | 11=18-x | | (7x+5)+(-8x+6)= | | 0.29=logx | | x=log(3)(48) | | 3/4t-6=1/3t-1 | | 3/2t-6=1/3t-1 | | nx+b=6(x-n)forx | | nx+b=6(x-n) | | 3x(x+4)=3(x-1) | | 70-1.5(4)= | | 6y-15=3y+6 |